Scutellarin inhibits caspase-11 activation and pyroptosis in macrophages via regulating PKA signaling - Jiezhou Ye; Bo Zeng; Meiyan Zhong; Hongchun Li; Lihui Xu; Junxiang Shu; Yaofeng Wang; Fan Yang; Chunsu Zhong; Xunjia Ye; Xianhui He; Dongyun Ouyang (Elsevier, 2021)
Inflammatory caspase-11 senses and is activated by intracellular lipopolysaccharide (LPS) leading to pyroptosis that has critical role in defensing against bacterial infection, whereas its excess activation under pathogenic circumstances may cause various inflammatory diseases. However, there are few known drugs that can control caspase-11 activation. We report here that scutellarin, a flavonoid from Erigeron breviscapus, acted as an inhibitor for caspase-11 activation in macrophages. Scutellarin dose-dependently inhibited intracellular LPS-induced release of caspase-11p26 (indicative of caspase-11 activation) and generation of N-terminal fragment of gasdermin D (GSDMD-NT), leading to reduced pyroptosis. It also suppressed the activation of non-canonical nucleotide-binding oligomerization domain-like receptor family pyrin domain containing 3 (NLRP3) inflammasome as evidenced by reduced apoptosis-associated speck-like protein containing a CARD (ASC) speck formation and decreased interleukin-1 beta (IL-1β) and caspase-1p10 secretion, whereas the NLRP3-specific inhibitor MCC950 only inhibited IL-1β and caspase-1p10 release and ASC speck formation but not pyroptosis. Scutellarin also suppressed LPS-induced caspase-11 activation and pyroptosis in RAW 264.7 cells lacking ASC expression. Moreover, scutellarin treatment increased Ser/Thr phosphorylation of caspase-11 at protein kinase A (PKA)-specific sites, and its inhibitory action on caspase-11 activation was largely abrogated by PKA inhibitor H89 or by adenylyl cyclase inhibitor MDL12330A. Collectively, our data indicate that scutellarin inhibited caspase-11 activation and pyroptosis in macrophages at least partly via regulating the PKA signaling pathway.